METODE COGNITIVE BEHAVIOUR THERAPY DALAM PENYEMBUHAN REMAJA PENGIDAP GANGGUAN MENTAL DI PUSAT PEMULIHAN KUANTAN PAHANG MALAYSIA - Izhan, Muhammad; Tanjung, Muaz; Daulay, Annisa Arrumaisyah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to explore the effectiveness of Cognitive Behavioral Therapy in treating an adolescent diagnosed with depression and erotomania. The subject experienced overwhelming emotions of worthlessness and regret, had difficulty concentrating, and had difficulty focusing. The method used in this research is the case study technique in this research is qualitative. This research uses a single case study or case study with a single level of analysis as its case study design. Data collection techniques were obtained through interviews, observations, psychological tests, and CBT evaluations during the study. The subject in this study is a 15-year-old adolescent in one of the Community Mental Health Centers (MENTARI), located at Jalan Masjid, 26100 Kuantan, Pahang, Malaysia. The results of the intervention showed that CBT helped the subject reduce the symptoms of depression and erotomania experienced by the subject. After undergoing the intervention, the subject experienced positive changes, such as reduced obsessive thoughts, improved emotion regulation, and better ability to control reactions to social situations. The subject also began to participate in daily activities again with a more realistic perspective of herself and her future.